2017
DOI: 10.1186/s11658-017-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of (+) taxifolin’s protective antioxidant effect for •OH-treated bone marrow-derived mesenchymal stem cells

Abstract: The natural dihydroflavonol (+) taxifolin was investigated for its protective effect on Fenton reagent-treated bone marrow-derived mesenchymal stem cells (bmMSCs). Various antioxidant assays were used to determine the possible mechanism. These included •OH-scavenging, 2-phenyl-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide radical-scavenging (PTIO•-scavenging), 1, 1-diphenyl-2-picryl-hydrazl radical-scavenging (DPPH•-scavenging), 2, 2′-azino-bis (3-ethylbenzo-thiazoline-6-sulfonic acid) radical-scavenging (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…The FRAP assay was initially established by Benzie and Strain . However, the experimental protocol was modified based on a previous report . Briefly, the FRAP reagent was prepared freshly by mixing 10 m m TPTZ, 20 m m FeCl 3 , and 0.29 m acetate–sodium acetate buffer (pH 3.6) in a ratio of 1:1:10.…”
Section: Methodsmentioning
confidence: 99%
“…The FRAP assay was initially established by Benzie and Strain . However, the experimental protocol was modified based on a previous report . Briefly, the FRAP reagent was prepared freshly by mixing 10 m m TPTZ, 20 m m FeCl 3 , and 0.29 m acetate–sodium acetate buffer (pH 3.6) in a ratio of 1:1:10.…”
Section: Methodsmentioning
confidence: 99%
“…The DPPH • probe, however, was recently suggested to have some limitations [35]. Nevertheless, DPPH • determination has successfully accumulated a great deal of evidence in computational [58,59] and experimental models [60][61][62]. More importantly, two tested-samples butein and (S)-butin could not be dissolved in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The belief that the catechol group in ring B of flavonoids is the major structural feature imparting antioxidant activity has been supported by the work of Jovanovic et al (1996). Topal et al (2016) and Li et al (2017) have reported that taxifolin is an effective antioxidant and antiradical by using indirect in vitro bioanalytical methods, including 1,1-diphenyl-2-picryl-hydrazyl radical-scavenging, 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) radical-scavenging, Fe 3+reducing and Cu 2+ -reducing assays. However, to our knowledge, there is no information concerning the types of ROS scavenged by taxifolin by using an ESR method.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2017) has reported that taxifolin is an effective scavenger of hydroxyl radical (•OH). The present study together with the report by Li et al (2017) indicates that taxifolin can be a scavenger of both ROO• and •OH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation